The Importance Role of Nurse Anesthetist for Cochlear Implantation - Mettapol, Chanisa; Hengphaisan, Saranya; Junyatham, Sirijunya (Journal of The Royal Thai Army Nurses, 2023)
Cochlear implant surgery is a procedure involving insertion a device into inner ear, as a treatment of congenital deafness or acquired deafness. The cochlear implant is a long operation, approach with microscope through ear canal. According to the usage of an intraoperative nerve stimulator, a neuromuscular blocking agent is prohibited. A specialized and skilled nurse anesthetist is essential to maintain the depth of anesthesia and promptly detection and treatment of any complications. Beginning with the preoperative period, the nurse anesthetist is responsible for patient assessment, patient preparation, and room setup. Moreover, intraoperative coordination with anesthesiologist and surgeon, postoperative monitoring for adequate pain control and treatment of immediate complications are the key success to acheive excellent patient care.